A Comprehensive Review of Immunosuppression Used for Liver Transplantation. (21st June 2009) - Mukherjee, Sandeep; Mukherjee, Urmila
Abstract : Since liver transplantation was approved for the treatment of end stage liver disease, calcineurin inhibitors (CNI's) have played a critical role in the preservation of allograft function. Unfortunately, these medications cause a variety of Side effects such as diabetes, hypertension and nephrotoxicity which in turn result in significant morbidity and reduced quality of life. A variety of newer immunosuppressants have been evaluated over the last decade in an attempt to either substitute for CNI's or use with reduced dose CNI's while still preserving allograft function However, current data does not recommend complete cessation of CNI's due to unacceptably high rates of allograft rejection. As these medications have their own unique adverse effects, a careful assessment on their risks and benefits is essential, particularly when additive or synergistic effects with CNI's may occur. Furthermore, the impact of these newer medications on the risk of hepatitis C recurrence and progression remains to be elucidated. Controlled trials are urgently required to assist transplant physicians with choosing the optimum immunosuppressive regimen for their patients. This review will discuss commonly used immunosuppressants prescribed in liver transplantation, emerging therapties and where appropriate, the impact of these medications on the recurrence of hepatitis C after liver transplantation.